Effect of Digital Health Education Towards Anxiety among Pre-Operative Patients: A Systematic Review - Daniel Nong Danche; Tintin Sukartini; Aria Aulia Nastiti; Ira Suarilah (Indonesian Journal of Global Health Research, 2024)
Anxiety is a major issue that worsens clinical symptoms and often arises when patients undergo surgery. However, the review of the impact of digital health education on pre-operative patients with anxiety is still limited. This study aimed to determine the effectiveness of digital health education in reducing anxiety in pre-operative patients. Methods: A systematic review of quantitative studies was conducted. Relevant full-text articles were sourced from four databases: Web of Science, Science Direct, Proquest, and PubMed, from January 1, 2019, to December 31, 2024. The quality of the included studies was assessed by the Joanna Briggs Institute (JBI). A narrative analysis was performed to present the effectiveness of digital health education on pre-operative patients with anxiety. Results: A total of 13 studies were identified, involving 1,394 pre-operative patients. The age of the participants ranged from 5 to 68 years. The effectiveness of digital health education for pre-operative patients with anxiety was seen as a mixed program combining images, audiovisual materials, and interactive features that allowed patients to communicate with each other and healthcare professionals. Conclusion: This study highlights that digital health education interventions are a promising avenue in healthcare delivery due to advancements in technology and information.